2010
DOI: 10.1509/jimk.18.3.62
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Differences in the Effect of Received Word-of-Mouth Referral in Relational Service Exchange

Abstract: Because of suggested beneficial effects of word-of-mouth (WOM) referral, service companies have invested large amounts of money in customer referral programs as well as programs aimed at fostering positive communication among their existing customers. The question of cross-cultural differences in the effectiveness of WOM has recently gained increased prominence. The authors contribute to research on this topic by proposing a positive effect of received WOM on service quality perceptions among existing customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 74 publications
3
74
2
3
Order By: Relevance
“…However, it is likely that the results of Kim and colleagues' (2010) study were impacted by the study's setting-the U.S. as trust, which is linked to gratitude (Palmatier et al, 2009), has been found to be influenced by national culture (e.g., Schumann et al, 2010). In addition, an implication derived from the academic literature is that there is a strong positive relationship between trust and collectivism, and a negative relationship between trust and individualism (e.g., Huff & Kelley, 2005).…”
Section: Gratitudementioning
confidence: 99%
“…However, it is likely that the results of Kim and colleagues' (2010) study were impacted by the study's setting-the U.S. as trust, which is linked to gratitude (Palmatier et al, 2009), has been found to be influenced by national culture (e.g., Schumann et al, 2010). In addition, an implication derived from the academic literature is that there is a strong positive relationship between trust and collectivism, and a negative relationship between trust and individualism (e.g., Huff & Kelley, 2005).…”
Section: Gratitudementioning
confidence: 99%
“…Neutral WOM is outside the scope of this study as it does not impact the consumers' behaviour (Wang, 2011). In the extant WOM consequence literature, the focus of research has been on firm related outcomes such as service quality perceptions (Schumann et al, 2010;Wang, 2011); loyalty (Garnefeld et al, 2011); commitment (Garnefeld et al, 2011); switching behaviour (Wangenheim & Bayon, 2004;2007) and purchase decisions (Bansal & Voyer, 2000;Brown & Reingen, 1987;East et al, 2008;East, Uncles & Lomax, 2014;Soderlund & Rosengren, 2007). In addition, Sweeney, Soutar and Mazzarol (2008) examined the psychological implications of received WOM on the recipient and found that the receipt of P-WOM increased relief, confidence and enthusiasm of the recipient.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Whilst single service settings have been successfully employed in past WOM research (Schumann et al, 2010;Soderlund & Rosengren, 2007;Wien & Olsen, 2014), future studies should test the model in multiple research settings in order to establish the generalizability of the findings.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 99%
“…However, the location of Kim and colleagues' (2010) study, the U.S., may have been impacted by national culture, as trust, which is linked to gratitude (Palmatier et al, 2009), has been found to be influenced by national culture (Doney, Cannon, & Mullen, 1998;Schumann et al, 2010). Also, Doney et al (1998) and Schumann et al (2010) revealed positive correlations between countries with a high power distance cultural dimension (i.e., the www.ccsenet.org/ijms…”
Section: Gratitudementioning
confidence: 95%
“…Also, Doney et al (1998) and Schumann et al (2010) revealed positive correlations between countries with a high power distance cultural dimension (i.e., the www.ccsenet.org/ijms…”
Section: Gratitudementioning
confidence: 99%